Uji Efektivitas Sediaan Facial Wash Acne Gel Ekstrak Etanol Daun Nangka (Artocarpus heterophyllus Lamk.) Terhadap Bakteri Staphylococcus aureus - Athaillah, Athaillah; Pritiwanti, Venni; Chandra, Putra; Affan Silalahi, Ali (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Jackfruit leaves (Artocarpus heterophyllus Lamk.) contain antimicrobial compounds such as flavonoids, tannins, and saponins, which can damage bacterial cytoplasmic membranes and denature cellular proteins. This potential supports the development of a facial wash gel using jackfruit leaf extract as a natural antibacterial alternative. Objective: This study aimed to evaluate the effectiveness of a facial wash gel containing jackfruit leaf extract (Artocarpus heterophyllus Lamk.) in inhibiting the growth of Staphylococcus aureus ATCC® 25923. Methods: This experimental study included sample preparation, identification, extraction, phytochemical screening, and gel formulation evaluation (organoleptic test, homogeneity, spreadability, foam height, pH, irritation, and cycling test). Antibacterial activity was tested against S. aureus, with a positive control (Himalaya (Brand) Facial Wash) and a negative control (DMSO). Results: The extract yield was 11.26%, positively detecting flavonoids, saponins, tannins, steroids, and triterpenoids. The gel formulations (F1-F3) were semi-solid, dark green, and had a characteristic jackfruit leaf aroma, with a pH of 5–6. Homogeneity tests confirmed uniform consistency, with the highest foam height in F3 (3.7 cm) and optimal spreadability in F1-F2 (6 cm). No irritation was observed, and the gel remained stable in cycling tests. The antibacterial test showed the highest inhibition at 12% extract concentration (92.3%), while the formulated gel also effectively inhibited S. aureus growth. Conclusion: Jackfruit leaves can be successfully formulated into a stable and safe facial wash gel with effective antibacterial activity against Staphylococcus aureus.